Breeding of a new high-quality, large-fruit, early-ripening and white-flesh loquat cultivar Zaobaixiang - DENG Chaojun; JIANG Jimou; XU Qizhi; CHEN Xiuping; HU Wenshun; SU Wenbing; ZHANG Yaling; CHEN Yongping; ZHENG Shaoquan (Guoshu xuebao)
Zaobaixiang is a novel variety of early-maturing, high-quality, large-fruit and white-fleshed loquat (Eriobotrya japonica Lindl.) selected from a cross between Zaozhong 6 and Xinbai 2. The varietal field test has been made in Fuzhou, Fujian since 2012. The regional experiments have been carried out in Fuzhou, Putian, of Fujian province and Hechuan Chongqing city since 2016. Zaobaixiang exhibites moderate to strong tree vigor with long and strong shoots. The single fruit weight is 57.1-66.1 g; the fruit shape is obovate or suborbicular, with a slanting or blunt base and a flattened tip; the color of pericarp is yellowish white to light orange red, with short and thin fuzz, few rust spots, distinct stripes and a high density of medium-sized fruit dots; the sepals are outwardly convex and the sepal hole is closed; the color of flesh is white to yellow-white, with a thickness of 8.9-10.8 mm; the content of soluble solids is 12.3%-15.8%, and the edible rate is 71.3%-76.4%; the flesh is melting, juicy, and sweet. The everage seed number is 4 to 5 per fruit. The early flowering stage is from late October to mid-November, the full blooming stage is from mid-November to early December, the final flowering period is in late December, and the fruits ripened in late March to mid-April. The variety is highly productive with strong resistance to adverse stresses. It is granted by the National Tropical Crops Aprroval Committee and is suitable to be cultivated in Fujian, Chongqing, Sichuan, Guangxi, Yunnan and other loquat producing areas.